2010
DOI: 10.1086/656558
|View full text |Cite
|
Sign up to set email alerts
|

Revised SHEA Position Paper: Influenza Vaccination of Healthcare Personnel

Abstract: Executive SummaryThis document serves as an update and companion piece to the 2005 Society for Healthcare Epidemiology of America (SHEA) Position Paper entitled “Influenza Vaccination of Healthcare Workers and Vaccine Allocation for Healthcare Workers During Vaccine Shortages.” In large part, the discussion about the rationale for influenza vaccination of healthcare personnel (HCP), the strategies designed to improve influenza vaccination rates in this population, and the recommendations made in the 2005 paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
125
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(136 citation statements)
references
References 43 publications
(32 reference statements)
2
125
0
9
Order By: Relevance
“…3 In 2010, the Society of Healthcare Epidemiology of America endorsed a policy requiring HCP annual influenza vaccination. 4 Since that time, many hospitals now require annual influenza vaccination as a condition of HCP employment, resulting in influenza vaccination coverage greater than 95%. 3,4 With only 62% of HCP reporting that their hospital employers require influenza vaccination, a significant number of hospitals have yet to adopt this recommendation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…3 In 2010, the Society of Healthcare Epidemiology of America endorsed a policy requiring HCP annual influenza vaccination. 4 Since that time, many hospitals now require annual influenza vaccination as a condition of HCP employment, resulting in influenza vaccination coverage greater than 95%. 3,4 With only 62% of HCP reporting that their hospital employers require influenza vaccination, a significant number of hospitals have yet to adopt this recommendation.…”
Section: Methodsmentioning
confidence: 99%
“…4 Since that time, many hospitals now require annual influenza vaccination as a condition of HCP employment, resulting in influenza vaccination coverage greater than 95%. 3,4 With only 62% of HCP reporting that their hospital employers require influenza vaccination, a significant number of hospitals have yet to adopt this recommendation. 3 HCP resistance to vaccination is an important barrier to hospitals requiring annual influenza vaccination and must be overcome to facilitate successful implementation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 And while SHEA's position paper clearly endorses mandatory vaccination programs, regarding mandatory masking policies SHEA "believes there is potential utility for this strategy" but cites potential logistical issues with enforcement. 9 What remained unclear, however, was whether both mandatory masking and mandatory vaccination programs could produce results that were equally sustainable and easily adaptable to all settings. Rakita et al 2 showed consistently high vaccination compliance with a mandatory vaccine program over a 5-year period.…”
Section: Sustaining High Influenza Vaccination Compliance With a Mandmentioning
confidence: 99%